Tourist risk perceptions and revisit intention: A critical review of literature - Md. Kamrul Hasan; Ahmed Rageh Ismail; MD. Faridul Islam (Cogent Business & Management, 2017)
Tourists' perceptions of risk with travel destination are one of the key determinants of their decision-making in revisiting a destination. Despite the importance of the subject in tourism literature, a few attempts have been made to focus on the effects of tourist risk perceptions on revisit intentions. Moreover, a theoretical foundation is still lacking in current literature highlighting the relationship of the effect of tourist risk perceptions through satisfaction and attitude towards revisiting with tourist revisit intention. Taking this into account as research gap, this paper provides a critical review of the effect of tourist risk perceptions in tourism research, presenting a descriptive background, identifying the progress, develop an integrated conceptual framework, review of their theoretical propositions and methodological issues and suggesting new areas and approaches for future research. The study concludes that the area is dominated by both the quantitative and the qualitative research, and a lack of appropriate theoretical foundation is a major problem to understand the common risk dimensions and their effect on tourist revisit intention. Therefore, the integration of satisfaction and attitude towards revisit with the relationship between tourist risk perceptions and revisit intention in a single framework seems rational to provide an insight for new research approach.
Keywords: 650